Hosting in turbulent times: hoteliers’ perceptions and strategies to recover from the Covid-19 pandemic - Herédia-Colaço, V.; Rodrigues, H. (International Journal of Hospitality Management, 2021)
This research examines hoteliers’ perceptions and strategies in light of the Covid-19 pandemic and their predictions about an uncertain industry that has shifted attention to safety and hygiene concerns to regain guests’ trust. A cross-sectional study comprised of four assessments with hoteliers worldwide (Nstudy 1 = 144; Nstudy2 = 100; Nstudy3 = 97; Nstudy4 = 66) was conducted between April and June 2020. Hoteliers’ forecasts and operating procedures were assessed in light of crisis management, providing important insights for researchers and the hotel industry. Remarkably, most of the hoteliers predict that the crisis is recoverable and believe that sales revenue will reach 2019 levels in 2021. They have implemented extraordinary recovery measures to make up for the loss of revenue caused by the crisis. From special health and safety protocols to long-term vouchers to promote reservations, strategic efforts to recover from the pandemic are ongoing.